2016
DOI: 10.1038/ncomms10942
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxygen reduction catalysed by Ni3(hexaiminotriphenylene)2

Abstract: Control over the architectural and electronic properties of heterogeneous catalysts poses a major obstacle in the targeted design of active and stable non-platinum group metal electrocatalysts for the oxygen reduction reaction. Here we introduce Ni3(HITP)2 (HITP=2, 3, 6, 7, 10, 11-hexaiminotriphenylene) as an intrinsically conductive metal-organic framework which functions as a well-defined, tunable oxygen reduction electrocatalyst in alkaline solution. Ni3(HITP)2 exhibits oxygen reduction activity competitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
525
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 637 publications
(536 citation statements)
references
References 50 publications
9
525
0
2
Order By: Relevance
“…ChemSusChem 2017, 10,4374 -4392 www.chemsuschem.org lysts. [116] NiCo-based thin MOF nanosheets, [108] aN iFe MOF array, [109] and an iron-cobalt carboxylate framework (Fe 3 -Co 2 ) [110] exhibit highere lectrocatalytic OER activity than commercial RuO 2 and IrO 2 .T hese examples demonstrate the viability of MOFs as alternatives to precious-metal-based heterogeneous electrocatalysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ChemSusChem 2017, 10,4374 -4392 www.chemsuschem.org lysts. [116] NiCo-based thin MOF nanosheets, [108] aN iFe MOF array, [109] and an iron-cobalt carboxylate framework (Fe 3 -Co 2 ) [110] exhibit highere lectrocatalytic OER activity than commercial RuO 2 and IrO 2 .T hese examples demonstrate the viability of MOFs as alternatives to precious-metal-based heterogeneous electrocatalysts.…”
Section: Discussionmentioning
confidence: 99%
“…[116] ICP-MSa nd atomic absorption spectroscopy (AAS) measurements of the films after potentiostatic measurements revealed the same Ni contentb efore and after electrolysis. XPS after electrolysis showed a + 1.0 eV increase in the bindinge nergy (BE) of the Ni 2p feature.…”
Section: Electrocatalytic Mofs For the Orrmentioning
confidence: 91%
“…[280] The polarization curve depicts that an onset potential of 0.82 V (vs RHE) was achieved for Ni 3 (HITP) 2 electrode measured in the O 2 -saturated solution, which is competitive with most of nonprecious metal catalysts. For example, Dinca and coworkers reported a conductive 2D layered MOF, i.e., Ni 3 (2,3, 6,7,10,11-hexaiminotriphenylene (HITP)) 2 , and then used as catalyst for ORR in alkaline electrolyte.…”
Section: Electrocatalysismentioning
confidence: 94%
“…We previously showed that the electrically conductive MOF Ni 3 (HITP) 2 (HITP = 2,3,6,7,10, (Figure 1) functions as …”
Section: ■ Introductionmentioning
confidence: 99%